Pengaruh Harga, Lokasi, dan Kualitas Pelayanan terhadap Kepuasan Pelanggan (Survey pada Bengkel Berguna Motor di Kota Cimahi) - Dede Hertina; Mochamad Hadidsyam Prawira Dirgasurya (Universitas Batanghari, 2023)
The existence of this rigorous test is intended to determine the effect of the variables Price, Location, and Quality of Service on Consumer Satisfaction at Serviceable Motor Workshops in Cimahi City. The data collected in this rigorous test came from distributing a questionnaire using a purposive sampling technique. A sample of 60 respondents was obtained. This research uses data instrument testing with validity and reliability tests. The hypothesis testing in this thorough test is to test multiple linear regression analysis, test the coefficient of determination, t test (partial), and f test (simultaneous). The results of the thorough test show that partially or based on a partial test, the variables Price, Location, and Service Quality have a significant influence on Customer Satisfaction. Based on the results, the F test shows the acquisition of Fcount of 96.681 > Ftable of 2.76, from this it shows that the three independent variables consisting of Price, Location, and Service Quality have a simultaneous effect on Consumer Satisfaction.